2015
DOI: 10.1148/radiol.14140468
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic Performance and Dose Comparison of Filtered Back Projection and Adaptive Iterative Dose Reduction Three-dimensional CT Enterography in Children and Young Adults

Abstract: CT enterography is highly accurate for detection of active inflammation in pediatric patients and has excellent interreader reliability. Reduced-dose CT enterography with AIDR 3D allowed substantial dose reduction compared with that used with FBP CT enterographic examinations, while maintaining a high diagnostic performance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
10
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 32 publications
3
10
0
Order By: Relevance
“…necessarily correlate with subjective image quality, as also shown in previous studies (6,9,33,34). IR in CT enterography reduces noise versus FBP at similar radiation exposures (17,32,33,35), which can alter the perceived subjective image sharpness (32). However, as was shown in our study, even half-dose images in patients with specific diagnoses such as active inflammatory terminal ileal Crohn disease have enough information to allow readers to formulate an accurate diagnosis.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…necessarily correlate with subjective image quality, as also shown in previous studies (6,9,33,34). IR in CT enterography reduces noise versus FBP at similar radiation exposures (17,32,33,35), which can alter the perceived subjective image sharpness (32). However, as was shown in our study, even half-dose images in patients with specific diagnoses such as active inflammatory terminal ileal Crohn disease have enough information to allow readers to formulate an accurate diagnosis.…”
Section: Discussionsupporting
confidence: 83%
“…The original CT enterographic protocol at our institution (in 2006) included scanning with a fixed 120 kVp and fixed quality reference milliampere second (200 for 16-section multidetector CT and 260 for 64-section multidetector CT), with automatic exposure control at strong increase for obese patients and weak decrease for slim patients (5). By changing to a weightbased reference milliampere second (1 pound [0.45 kg] = 1 mAs) and changing the automatic exposure control settings to a weak increase for obese patients and a strong decrease for slim patients, we were able to achieve a substantial dose reduction of about 32% (16-section multidetector CT) to 41% (64-section multidetector CT) (to date, the main strategies for reducing radiation dose in CT enterography have included using appropriate automatic exposure control, lowering kilovolt peak, using weight-based protocols, and applying IR techniques) (6,31,32). In our study, we evaluated whether dose reductions with IR could result in lower doses without affecting diagnostic accuracy in this patient population.…”
Section: Discussionmentioning
confidence: 94%
“…In the pediatric population, estimated effective doses as low as 2.94 mSv have been reported for abdominal CT using multiple detector computed tomography [6] and varied 64320 detector CT scanners [17] . Newer adaptive iterative dose reduction techniques have been described that greatly reduce the radiation exposure among pediatric patients undergoing CTE from 16.7 milligray (mGy) to 6.1 mGy, with minimal reduction in diagnostic sensitivity and specificity [18] . Similarly, newly proposed CTE imaging techniques using lowdose radiation and noise reduction techniques among adults can reduce effective dose radiation exposure by 53%60% from 1520 mSv to 57 mSv [19] .…”
Section: Ctementioning
confidence: 99%
“…These improvements, whatever the anatomical region examined, make it possible to reduce exposure parameters, hence decreasing patient radiation dose. Many authors therefore consider that they are a suitable alternative to FBP [1][2][3][4][5][6][7][8].In this issue of Diagnostic and Interventional Imaging, Pontana et al reported a novel approach for assessing the impact of IR on CT pulmonary angiography [9]. In their article, the authors evaluated CT angiograms obtained with a dual-source CT unit.…”
mentioning
confidence: 99%
“…These improvements, whatever the anatomical region examined, make it possible to reduce exposure parameters, hence decreasing patient radiation dose. Many authors therefore consider that they are a suitable alternative to FBP [1][2][3][4][5][6][7][8].…”
mentioning
confidence: 99%